Co-expression of nitrogenase proteins in cotton (Gossypium hirsutum L.). - Yimin Shang; Wenfang Guo; Xiaomeng Liu; Lei Ma; Dehu Liu; Sanfeng Chen (PLoS ONE, 2023)
Chemical nitrogen fertilizer can maintain crop productivity, but overuse of chemical nitrogen fertilizers leads to economic costs and environmental pollution. One approach to reduce use of nitrogen fertilizers is to transfer nitrogenase biosynthetic pathway to non-legume plants. Fe protein encoded by nifH and MoFe protein encoded by nifD and nifK are two structural components of nitrogenase. NifB encoded by nifB is a critical maturase that catalyzes the first committed step in the biosynthesis of nitrogenase FeMo-cofactor that binds and reduces N2. Expression of the nifB, nifH, nifD and nifK is essential to generate plants that are able to fix atmospheric N2. In this study, the four genes (nifB, nifH, nifD and nifK) from Paenibacillu polymyxaWLY78 were assembled in plant expression vector pCAMBIA1301 via Cre/LoxP recombination system, yielding the recombinant expression vector pCAMBIA1301-nifBHDK. Then, the four nif genes carried in the expression vector were co-introduced into upland cotton R15 using Agrobacterium tumefaciens-mediated transformation. Homozygous transgenic cotton lines B2, B5 and B17 of T3 generation were selected by PCR and RT-PCR. qRT-PCR showed that nifB, nifH, nifD and nifK were co-expressed in the transgenic cottons at similar levels. Western blotting analysis demonstrated that NifB, NifH, NifD and NifK were co-produced in the transgenic cottons. Co-expression of the four critical Nif proteins (NifB, NifH, NifD and NifK) in cottons represents an important step in engineering nitrogenase biosynthetic pathway to non-legume plants.